SYNTHESIS OF ETHYL FATTY ALKYL ETHERS FROM COCONUT (Cocos nucifera L.) FATTY ALCOHOLS - Acabal, Alice R.M.; Padolina, William G. (Annals of Tropical Research, 1987)
Ethyl fatty alkyl ethers were synthesized using coconut fatty alcohols as the starting raw materials. The fatty alcohols were converted into their corresponding bromides which were then made to react with ethanolic potassium hydroxide. The average percent yield of ethyl fatty alkyl ethers was 74.30%. The products were characterized using chemical tests, infrared (ir) spectrophotometry, and proton magnetic resonance (pmr) spectroscopy.